Penerapan media Erfolgreich digital Deutsch Unterrichten untuk pembelajaran daring di SMA Negeri 8 Malang - Griandini, Margaretha Inez; Ardiyani, Dewi Kartika (2020)
This research is conducted to describe the implementation of Erfolgreich Digital Deutsch Unterrichten in online german lesson at SMA Negeri 8 Malang and the problem that is experienced in it. EDDU provides digital learning ideas for german teachers. The main idea of EDDU is to help german teachers in utilizing digital medias like smartphone and its functions (especially social media which also used by the students on daily basis) in german lesson. Based on the data analysis, the implementation of EDDU could help the teacher in organizing an interesting, and fun german lesson. The result of this study shows that the implementation of EDDU was going well and more interactive. Even though there are a few students who didn't actively participated, the implementation of the idea from EDDU makes the learning activity more effective since the students are enthusiast.